Correlative STED and Atomic Force Microscopy on Live Astrocytes Reveals Plasticity of Cytoskeletal Structure and Membrane Physical Properties during Polarized Migration - Curry, Nathan; Ghézali, Grégory; Kaminski Schierle, Gabriele S.; Rouach, Nathalie; Kaminski, Clemens F. (Frontiers in Cellular Neuroscience, 2017)
The plasticity of the cytoskeleton architecture and membrane properties is important for the establishment of cell polarity, adhesion and migration. Here, we present a method which combines stimulated emission depletion (STED) super-resolution imaging and atomic force microscopy (AFM) to correlate cytoskeletal structural information with membrane physical properties in live astrocytes. Using STED compatible dyes for live cell imaging of the cytoskeleton, and simultaneously mapping the cell surface topology with AFM, we obtain unprecedented detail of highly organised networks of actin and microtubules in astrocytes. Combining mechanical data from AFM with optical imaging of actin and tubulin further reveals links between cytoskeleton organisation and membrane properties. Using this methodology we illustrate that scratch-induced migration induces cytoskeleton remodelling. The latter is caused by a polarization of actin and microtubule elements within astroglial cell processes, which correlates strongly with changes in cell stiffness. The method opens new avenues for the dynamic probing of the membrane structural and functional plasticity of living brain cells. It is a powerful tool for providing new insights into mechanisms of cell structural remodeling during physiological or pathological processes, such as brain development or tumorigenesis.